The Importance of the Ability to Pay Principlein the Ecuadorian Tax Regime - Armijos González, Pedro Orlando (2021)
The Constitution of the Republic of Ecuador, in its article three hundred, has not included the ability to pay principle as one of the principles that shape the natio-nal tax regime. However, the Ecuadorian Constitutional Court, through several rulings, has issued statements of great value on the importance of this principle, affirming that it constitutes the transversal axis that is based on the obligation to pay taxes; even being considered as the ground of the amount of contributions, and the limit of the tax burden. This principle seeks to make people contribute to the financing of public spending in an adequate way, according to their real capacity, as long as there are manifestations of demonstrable wealth, that is why the lawmaker at the time of the formation of a new levy, finds himself in the obligation to consider it. The importance of this maxim for the Ecuadorian Tax Regime is undeniable, since it stands as guarantee of the subjects, preventing the sources of wealth from being disrupted with the establishment of excessive loads that could ultimately be considered unconstitutional, because of putting at risk the tax harmony that involves the interrelation of constitutional principles, including the ability to pay principle.